Changes in retinal nerve fiber layer thickness measurements in response to a trifocal intraocular lens implantation. (October 2018) - García-Bella, Javier; Talavero-González, Paula; Carballo-Álvarez, Jesús; Sanz-Fernández, Juan; Vázquez-Moliní, José; García-Feijóo, Julián; Martínez-de-la-Casa, José
Abstract Aims To determine the changes produced on the peripapillary retinal nerve fiber layer (RNFL) thickness, measured by an spectral-domain optical coherence tomography (OCT), after the implantation of a trifocal diffractive intraocular lens (IOL) and compare them with the variations produced by a monofocal IOL implantation. Methods A prospective, double masked study in which 50 eyes belonging to 50 patients with bilateral cataract were enrolled. Sequentially, the first 25 patients were bilaterally implanted with the trifocal diffractive IOL AT LISA® Tri 839 MP and the following 25 patients with the monofocal IOL CT ASPHINA® 409 M/MP. RNFL thickness measurements were performed by Cirrus HD®-OCT before and six months after the second eye surgery. Results Mean patient age was 69.5 ± 6.1 years. In response to surgery, the average RNFL thickness increased 7.29 ± 10.51 µm at the AT LISA® Tri group and 1.96 ± 2.90 µm at the monofocal IOL group from the baseline (p  = 0.017). Statistically significant differences in thickness variations were also detected in the superior sector (7.86 ± 7.70 µm at the AT LISA® Tri group vs 1.73 ± 5.74 µm at the monofocal group). Statistically significant differences between the pre and the postsurgery measurements were found in all sectors except the inferior one with the trifocal IOL and in two of the studied sectors (average and temporal) with the monofocal IOL. Conclusions The IOL implantation produce changes in the RNFL thickness, which are larger in case of a trifocal diffractive IOL.